Diverse Mechanisms Regulate the Surface Expression of Immunotherapeutic Target CTLA-4 - Schneider, Helga; Rudd, Christopher E. (Frontiers in Immunology, 2014)
T-cell co-receptor cytotoxic T-cell antigen 4 (CTLA-4) is a critical inhibitory regulator of T-cell immunity and antibody blockade of the co-receptor has been shown to be effective in tumor immunotherapy. Paradoxically, the majority of CTLA-4 is located in intracellular compartments from where it is transported to the cell surface and rapidly internalized. The intracellular trafficking pathways that control transport of the co-receptor to the cell surface will ensure the appropriate balance of negative and positive signaling for a productive immune response with minimal autoimmune disorders. It will also influence the degree of inhibition and the potency of antibody checkpoint blockade in cancer immunotherapy. Current evidence indicates that the mechanisms of CTLA-4 transport to the cell surface and its residency are multifactorial involving a combination of immune cell specific adaptors such as TRIM and LAX, the small GTPase Rab8 as well as generic components such as ARF-1, phospholipase D (PLD) and the heterotetrameric AP1/2 complex. This review covers the recent developments in our understanding of the processes that control the expression of this important co-inhibitory receptor for the modulation of T-cell immunity. Interference with the processes that regulate CTLA-4 surface expression could be an alternate therapeutic approach in the treatment of cancer and autoimmunity.